Perancangan Sistem Manajemen Mutu Produk Kemasan di PT. X - Elbert Giovanni; Felecia Felecia (Jurnal Titra, 2022)
PT. X is a company that is growing on a large scale and requires process control in product design activities to reduce product defects. The research was conducted with the aim of designing a quality management system in the TTPI department at PT. X. The research focuses on the design of packaging products. The quality management system is designed to minimize the impact of packaging product defects such as poor product functionality, specifications that are not in accordance with demand and others. There were 10 types of packaging defects found. The design is using the DMAIC method and the analysis using 5 whys analysis. 10 packaging defects have root causes, namely measurement errors, color determination, finishing, and different understandings with vendors. The proposed improvements are in the form of a sequential control process from making print files (die line), requesting and reviewing the results of raw designs, semi-finished designs and finished designs from vendors. This improvement proposal is controlled by making SOPs, vendor visits, standardization of measuring instruments and colors. From the suggested improvements, it is considered that can be used as a step to anticipate errors in packaging product specifications and the product design process to be more structured.